2022
DOI: 10.1089/jwh.2021.0447
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Among Patients with Physical Disability

Abstract: Background: Pap smear has a central role in cervical cancer screening. Previous studies have found that female patients with disabilities are less likely to receive a Pap smear as recommended by guidelines. The aim of our study was to examine the association between physical disability and Pap smear receipt in Israel. Methods: This cross-sectional study was conducted using the electronic medical records of the second largest health care maintenance organization in Israe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Some potential reasons for the lower rates of cervical cancer screening among women with an independent living disability, ambulatory disability and multiple disabilities may be physical barriers including inability to access exam tables, 31 environmental barriers including lack of transportation or caregivers, 32 individual factors including older age, lack of health insurance, severe depression and other mental health conditions including anxiety; interpersonal factors including poor access to physician or poor communication with healthcare providers and spousal support. 33,4 We found evidence that receipt of cervical cancer screening with Pap test differed by disability type. Speci cally, the study found that, compared to women with no disabilities, women with multiple and ambulatory disabilities were less likely to receive cervical cancer screening with Pap test after controlling for risk factors associated with cervical cancer screening.…”
Section: Discussionmentioning
confidence: 81%
“…Some potential reasons for the lower rates of cervical cancer screening among women with an independent living disability, ambulatory disability and multiple disabilities may be physical barriers including inability to access exam tables, 31 environmental barriers including lack of transportation or caregivers, 32 individual factors including older age, lack of health insurance, severe depression and other mental health conditions including anxiety; interpersonal factors including poor access to physician or poor communication with healthcare providers and spousal support. 33,4 We found evidence that receipt of cervical cancer screening with Pap test differed by disability type. Speci cally, the study found that, compared to women with no disabilities, women with multiple and ambulatory disabilities were less likely to receive cervical cancer screening with Pap test after controlling for risk factors associated with cervical cancer screening.…”
Section: Discussionmentioning
confidence: 81%
“…Although the number of routine physician visits did not differ by disability status, frequency of these visitsmay not reflect adequacy of preventive care, as prior studies found reduced rates of screening among people with disabilities [33][34][35], sometimes well below those recommended by the US Preventive Services Task Force [10]. Lower preventive care among those with a physical disability may be due to personal factors (anxiety), social factors (poor communication with providers, feeling of inadequate support), provider factors (prioritizing acute problems over chronic comorbid conditions), or environmental factors (inaccessible exam tables and other physical access barriers) [36][37][38].…”
Section: Discussionmentioning
confidence: 94%
“…Physical disability can make it more difficult to access or attend screening. Barriers can include a lack of wheelchair access, problems getting onto the examination couch for the test, and previous misunderstandings, dismissal, and negative experiences of cervical cancer screening 66,67 Not understanding current cervical cancer screening guidelines 68 …”
Section: Main Barriers To Cervical Cancer Screening Participation And...mentioning
confidence: 99%